Analisis Kesalahan Sintaksis dan Morfologi Menggunakan Kitab Af’alul Yaumiyyah di Lembaga Pengembangan Bahasa Arab Tingkat Mutawassith - Abdullah, Ahmad Hafidz; Sholeh, Farhanudin (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
Understanding grammar (syntax) and verb forms (morphology) is fundamental to achieving proficiency in the Arabic language, particularly at the intermediate (Mutawassith) level, where all four language skills are taught in a balanced manner. This implies that students must be able to comprehend and apply these concepts in constructing correct sentences. However, this aspect is rarely explored in research on the Mutawassith level, despite the expectation that students should independently develop their ability to design and use new sentences.This study aims to identify and analyze recurring syntax and morphology errors and investigate their underlying causes among Mutawassith-level students. The research adopts a descriptive qualitative approach, with primary data sources consisting of teachers and students from an Arabic language development program at Pondok Pesantren Walisongo Wonokerto Tekung Lumajang, which uses the “Kitab Af’alul Yaumiyyah” as a key reference for studying syntax and morphology. Data collection techniques include direct classroom observation and interviews. Data analysis follows the Miles and Huberman model.The results of the study reveal five frequent and recurring errors, including four syntax errors and one morphology error. The primary cause of these errors is the students’ inconsistency in practicing sentence construction, leading to a failure to internalize syntax and morphology rules accurately. Keywords: Error Analysis, Syntax and Morphology, Intermediate Level